(untitled) (Asian Journal of Medical Sciences, 2024)
Background: Endoscopic biliary stenting is a common procedure in gastroenterology that uses plastic stents for short-term bile drainage. Aims and Objectives: This study explores the occurrence and consequences of forgotten or retained biliary stents. Materials and Methods: Conducted at King George Hospital in Visakhapatnam over 8 months, the study includes 12 patients with forgotten biliary stents. Diagnostic confirmation used X-rays, abdominal ultrasound, and magnetic resonance cholangiopancreatography. Four patients faced complications such as fractured distal pigtails and blocked stents, making retrieval challenging through standard methods like endoscopic retrograde cholangiopancreatography (ERCP) and cholangioscopy. Results: The study involved 12 patients (median age: 48 years), with choledocholithiasis being the main reason for stent placement in 10 cases (83.3%). On average, patients showed symptoms 31.3 months after stenting, mostly presenting with cholangitis (83.3%). Stent removal was successful in 8 cases (66.6%) using ERCP, while advanced procedures like cholangioscopy or surgery were needed in the rest. No mortality was reported. Conclusion: Conducted during the COVID-19 pandemic, this study reveals a rise in neglected plastic biliary stents. Cholangitis, often with common bile duct stones, was a common complication. Standard ERCP techniques were less effective in cases with complicated stents, requiring alternative approaches like cholangioscopy or surgery. The cases emphasize the urgency of timely stent retrieval and the need to improve management protocols to prevent complications.